EGF-Induced miR-223 Modulates Goat Mammary Epithelial Cell Apoptosis and Inflammation via ISG15 - Zhang, Yue; Wu, Qiong; Niu, Guanglin; Liu, Jidan; Cao, Fangjun; An, Xiaopeng; Cao, Binyun (Frontiers in Cell and Developmental Biology, 2021)
The health of mammary gland is essential for lactation. Epidermal growth factor (EGF) is reported to play an important role in lactation initiation and miR-223 is a conserved microRNA in anti-inflammation. In this study, EGF was found to induce a higher expression of miR-223 in goat mammary epithelial cell (gMEC). The downstream genes of miR-223 were screened by RNA sequencing, including Interferon-stimulated gene product 15 (ISG15), a pivotal immune responder, which was detected to be downregulated by EGF and miR-223. Due to the correlation between inflammation and apoptosis, the gMEC apoptosis modulated by EGF, miR-223 and ISG15 was investigated, and the protein expressions of Bcl-2/Bax, Caspase3 and p53 were examined to evaluate the apoptosis of gMEC. The protein expressions of p-STAT3/STAT3, PR, FOXC1 and HOXA10, which had been shown to be related to inflammation, were detected to assess the inflammation of gMEC. This study provided a regulation axis, EGF/miR-223/ISG15, and illustrated its regulation to gMEC apoptosis and inflammation.